Mental health providers are inexperienced but interested in telehealth-based virtual reality therapy: survey study - Ong, Triton; Barrera, Janelle F.; Sunkara, Charvi; Soni, Hiral; Ivanova, Julia; Cummins, Mollie R.; Schuler, Kaitlyn R.; Wilczewski, Hattie; Welch, Brandon M.; Bunnell, Brian E. (Frontiers in Virtual Reality, 2024)
Virtual reality (VR) is an emerging technology that can enhance experiences and outcomes in mental health care. However, mental health therapists have been slow to adopt VR into practice. Implementation of telehealth-based VR therapy (tele-VR) could catalyze adoption and innovation in mental health care. To explore therapists' perspectives on tele-VR, we conducted a cross-sectional survey of practicing mental health providers in the United States in June-July 2023. We analyzed 176 completed surveys from therapists, of whom 51.14% had no prior experience with VR, only 6.25% had used VR clinically, and 56.82% had neutral impressions of VR for therapy. Despite therapists' general inexperience with VR, therapists indicated a wide variety of tele-VR simulations (e.g., social situations, flying, heights) and features (e.g., personalized spaces, homework, interactivity) would be moderately to extremely useful for their practices. Therapists also requested additional VR simulations and features for their telehealth clients such as behavioral skills training, exposure therapy, gender identity therapy, and psychological assessments in VR. Therapists rated Health Insurance Portability and Accountability Act compliance, the ability to try VR before buying, affordability for therapists, accessibility for clients, and insurance coverage as the five most influential implementation factors for tele-VR. Overall, therapists were generally inexperienced and neutral about VR for telehealth therapy, but were interested in tele-VR for specific applications. These findings provide actionable directions for future research and collaborative development of therapeutic VR content and features.